Approximate Solutions of Fractional Nonlinear Equations Using Homotopy Perturbation Transformation Method - Yanqin Liu (Abstract and Applied Analysis)
A homotopy perturbation transformation method (HPTM) which is based on homotopy perturbation method and Laplace transform is first applied to solve the approximate solution of the fractional nonlinear equations. The nonlinear terms can be easily handled by the use of He's polynomials. Illustrative examples are included to demonstrate the high accuracy and fast convergence of this new algorithm.